AUGMENTED REALITY-BASED VIRTUAL LABORATORY APPLICATION AS CHEMISTRY LEARNING MEDIA FOR ACID-BASE TITRATION MATERIAL - Tania, Andini Putri; Sukarmin, Sukarmin (Universitas Labuhanbatu, 2025)
Purpose – This research aims to develop an augmented reality-based virtual laboratory application that is feasible as a chemistry learning media for acid-base titration material, assessed as valid, practical, and effective.Methodology – This study is a type of research and development using the 4D (Define, Design, Develop, and Disseminate) model, which is limited to the development stage only. The research was conducted at SMAN 2 Sidoarjo with 40 science students of class XI as the limited trial subjects. Data were collected from validation questionnaires, student response questionnaires, student activity observation sheets, and learning outcome tests, such as pretest and posttest. Descriptive quantitative methods were used to analyze the data.Findings – Validity results show that the developed application is valid with a mode score of 4 (good category) on both content and construct validity. Practicality analysis shows that the developed application is efficient, with an average percentage of student responses of 96% and a relevant student activity percentage of 93,32%, both of which fall into the outstanding category. Effectiveness analysis based on the Wilcoxon signed-rank test results revealed a significant difference between the pretest and posttest scores, with a significance value obtained of 0,000 (which is less than the significance value of 0,05), indicating that the developed application is efficacious in improving students’ learning outcomes. Therefore, it is concluded that the augmented reality-based virtual laboratory application developed is feasible as a chemistry learning medium for acid-base titration material.Contribution – An innovative chemistry learning media that facilitates a more visual and interactive understanding of the acid-base titration concept, providing an alternative solution to overcome limited laboratory facilities in schools and supporting more efficient implementation of chemistry practicum activities.